2016
DOI: 10.11646/phytotaxa.259.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships in Trichilia (Meliaceae) Based on Ribosomal Its Sequences

Abstract: The internal transcribed spacer (ITS) region of ribosomal DNA (rDNA) was used to investigate phylogenetic relationships in Trichilia (Meliaceae). Analyses focused on the neotropical Trichilia and consisted of 112 accessions (95 neotropical Trichilia, 6 African Trichilia and 11 Meliaceae Outgroups). Bayesian and Parsimony approaches demonstrated that the Cuban species T. havenensis is the earliest diverging lineage in the genus. The African species of Trichilia are nested within the neotropical clade. Section M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…It is sometimes suggested that the evolutionary history of Meliaceae has been one of radiation. Koenen et al (2015) concluded that the family as a whole evolved by "recent radiations", while Pennington & Clarkson (2013) proposed recent radiation in Guarea, Clarkson et al (2016) proposed "recent rapid radiation" in Trichilia, and Grudinski et al (2014a) discussed the "major radiation" in Aglaia Lour.…”
Section: Have Meliaceae Evolved By Radiation?mentioning
confidence: 99%
See 4 more Smart Citations
“…It is sometimes suggested that the evolutionary history of Meliaceae has been one of radiation. Koenen et al (2015) concluded that the family as a whole evolved by "recent radiations", while Pennington & Clarkson (2013) proposed recent radiation in Guarea, Clarkson et al (2016) proposed "recent rapid radiation" in Trichilia, and Grudinski et al (2014a) discussed the "major radiation" in Aglaia Lour.…”
Section: Have Meliaceae Evolved By Radiation?mentioning
confidence: 99%
“…Notes. An initial molecular phylogeny indicated that Trichilia sensu lato comprises three main clades (Clarkson et al, 2016): with a phylogeny Trichilia havanensis of America (35 American Trichilia species (6 African Trichilia species, Pseudobersama + Pterorrhachis, both from Africa, and T. trifolia of America)).…”
Section: Malleastrum (Baill) J-fleroymentioning
confidence: 99%
See 3 more Smart Citations